2022
DOI: 10.3390/jpm12020285
|View full text |Cite
|
Sign up to set email alerts
|

HBV Reactivation in Patients with Past Infection Affected by Non-Hodgkin Lymphoma and Treated with Anti-CD20 Antibody Based Immuno-Chemotherapy: A Multicenter Experience

Abstract: Hepatitis B virus reactivation (HBVr) can develop in HBV surface antigen (HBsAg) positive or HBsAg-negative and anti-hepatitis B core antigen antibodies (anti-HBc) positive (past HBV infection) patients receiving immuno-chemotherapy for hematological malignancies. A higher rate of HBVr is associated with the use of rituximab (R) in patients with past HBV infection, thus justifying an antiviral prophylaxis. In this study we evaluated the incidence of HBVr in a real-life cohort of 362 anti-HBc-positive subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…HBV reactivation is a substantial risk for patients with isolated HBcAb positive receiving rituximab-containing chemotherapy. Studies (8)(9)(10)(11)(12) showed that the incidence of HBV reactivation was 3%-68.3% in patients with isolated HBcAb positive who didn't take prophylactic antiviral therapy while receiving rituximab. The incidence of liver failure after HBV reactivation ranges from 0% to 37.5%, resulting in a mortality rate of 0% to 12.5% (11,13,14).…”
Section: Discussionmentioning
confidence: 99%
“…HBV reactivation is a substantial risk for patients with isolated HBcAb positive receiving rituximab-containing chemotherapy. Studies (8)(9)(10)(11)(12) showed that the incidence of HBV reactivation was 3%-68.3% in patients with isolated HBcAb positive who didn't take prophylactic antiviral therapy while receiving rituximab. The incidence of liver failure after HBV reactivation ranges from 0% to 37.5%, resulting in a mortality rate of 0% to 12.5% (11,13,14).…”
Section: Discussionmentioning
confidence: 99%